Seven years of external control of fluoride levels in the public water supply in Bauru, Sao Paulo, Brazil - Marilia Afonso Rabelo BUZALAF; Camila Mascarenhas MORAES; Kelly Polido Kaneshiro OLYMPIO; Juliano Pelim PESSAN; Larissa Tercilia GRIZZO; Thelma Lopes SILVA; Ana Carolina MAGALHAES; Rodrigo Cardoso de OLIVEIRA; Sonia GROISMAN; Irene RAMIRES (University of São Paulo, 2013)
Fluoridation of the public water supplies is recognized as among the top ten public health achievements of the twentieth century. However, the positive aspects of this measure depend on the maintenance of fluoride concentrations within adequate levels. Objective To report the results of seven years of external control of the fluoride (F) concentrations in the public water supply in Bauru, SP, Brazil in an attempt to verify, on the basis of risk/benefit balance, whether the levels are appropriate. Material and Methods From March 2004 to February 2011, 60 samples were collected every month from the 19 supply sectors of the city, totaling 4,641 samples. F concentrations in water samples were determined in duplicate, using an ion-specific electrode (Orion 9609) coupled to a potentiometer after buffering with TISAB II. After the analysis, the samples were classified according to the best risk-benefit adjustment. Results Means (±standard deviation) of F concentrations ranged between 0.73±0.06 and 0.81±0.10 mg/L for the different sectors during the seven years. The individual values ranged between 0.03 and 2.63 mg/L. The percentages of the samples considered "low risk" for dental fluorosis development and of "maximum benefit" for dental caries prevention (0.55-0.84 mg F/L) in the first, second, third, fourth, fifth, sixth, and seventh years of the study were 82.0, 58.5, 37.4, 61.0, 89.9, 77.3, and 72.4%, respectively, and 69.0% for the entire period. Conclusions Fluctuations of F levels were found in the public water supply in Bauru during the seven years of evaluation. These results suggest that external monitoring of water fluoridation by an independent assessor should be implemented in cities where there is adjusted fluoridation. This measure should be continued in order to verify that fluoride levels are suitable and, if not, to provide support for the appropriate adjustments.